Metal Nanoparticles as Catalysts for Green Applications - Signoretto, Michela; Menegazzo, Federica (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint of "Metal Nanoparticles as Catalysts for Green Applications" collects recent works of researchers on metal nanoparticles as catalysts for green applications. All works deal with designing chemical products and processes that generate and use less (or preferably no) hazardous substances by applying the principles of green chemistry. Despite the interdisciplinary nature of the different applications involved, ranging from pure chemistry to material science, from chemical engineering to physical chemistry, in this reprint there are common characteristics connecting the areas together, and they can be described by two words: sustainability and catalysis.